The effects of unripe saba banana composite flour on acceptance and physicochemical characteristics of biscuits / Shareenie Mariely Ayu … [et al.] - Mariely Ayu, Shareenie; Matkhir, Afham Aisyah; Akanda, Jahurul Haque; Mamat, Hasmadi; Abdul Hamid, Mansoor (UiTM Press for the Research Management Center (IRMI), Universiti Teknologi MARA, 2021)
Biscuits are a popular staple food due to its variety of taste, crispiness and digestibility. Conventional biscuits are rich in carbohydrates, fats and calories but low in dietary fibre (DF), minerals and vitamins. Unripe banana contains high resistant starch (RS) which is beneficial for colon health and helps reduce the risk of cardiovascular diseases and diabetes. This study was conducted to determine the feasibility of substituting wheat flour (WF) with unripe Saba banana flour (USBF) to produce biscuits with sensory acceptance and characterising its physicochemical properties. A total of nine (9) formulations were developed by incorporating WF with USBF (10- 90%). These formulations were tested for sensory acceptance with the best formulation then proceeded for physicochemical analysis. Sample F5 (50% USBF and 50% WF) was chosen as the best formulation and compared with the control biscuit (100% WF) for physicochemical characteristics. The comparison results showed that F5 biscuit had significant increment .,